Board Diversity, Audit Oversight, and Intellectual Capital in Corporate Performance - Muhammad Rizqi Alriansyah Manurung; Anwar Hariyono; Juli Riyanto Tri Wijaya (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Corporate performance is a key issue in corporate governance research as it reflects a company’s ability to create value and maintain competitiveness. Specific Background: Governance mechanisms, including audit committees and board characteristics such as the gender and age of directors, are considered important in shaping corporate performance, whilst intellectual capital is increasingly viewed as a strategic resource for value creation. Knowledge Gap: Previous research has largely examined governance and intellectual capital variables in isolation, with limited evidence regarding the integration of these variables within a single model and the testing of the moderating role of intellectual capital. Objectives: This study examines the influence of the audit committee, directors’ gender and directors’ age on firm performance and tests whether intellectual capital acts as a moderator in these relationships. Method: Using a quantitative approach, this study analyses secondary data from 32 manufacturing companies listed on the Indonesia Stock Exchange over the period 2021–2024 using PLS-SEM with SmartPLS 4 software. Results: Directors’ gender and intellectual capital have a positive and significant effect on firm performance, whilst the audit committee, directors’ age, and all interaction terms are not significant. Novelty: This study integrates various governance and intellectual capital variables within a single framework. Implications: Firms should strengthen gender diversity and intellectual capital to improve performance.